March of the sandbots. - Goldman, D.
Goldman at Georgia Tech, Koditschek and Komsuoglu at the University of Pennsylvania, in Philadelphia, and other collaborators - are hoping that by studying the zebra-tailed lizard and a menagerie of other desert-dwelling creatures, we can create more agile versions of their six-legged robot, SandBot.
Keywords: SandBot; Crescent-shaped feet; Desert dwelling creatures; Fluid behavior; Glass beads; Sandy terrain; Six-legged robot; Solid behavior; Zebra tailed lizard